Readiness of Islamic Boarding School-Based Education Personnel in Modern School Administration in South Sumatera Province - Umar, Saiful (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2023)
Pesantren-based educational institutions practically refer to the approach of the national curriculum and compilation with the curriculum of the Ministry of Religion and the local curriculum which is the policy of each pesantren. The pesantren curriculum tends to be conventional, influenced by salafi principles, which are still considered relevant to today's conditions. This study aims to measure the readiness of education personnel in efforts to modernize Islamic boarding school-based educational institutions, as well as to map the potential for administrative readiness and institutional management. This quantitative research uses an exportatory descriptive approach, taking 9 educational institutions at the SD/MI and SMP/MTs levels in South Sumatra Province. Respondents are educational staff, both teachers and administrative and management staff. The analysis was carried out with inferential statistics to measure the level of school readiness. The results of the study indicate that the education staff has a relatively ready readiness, both education staff at the SD/MI and SMP/MTs levels. It can be said that education staff have shown their readiness to modernize administration in school management, although there are almost differences in the pattern of readiness at each level, which in education staff at the SD/MI level is more visible in behavioral readiness and emotional attitudes, and in educational staff at the SD/MI level. SMP/MTs level education shows more readiness in thinking and readiness from emotional attitudes.